Epidemiological, Molecular, and Clinical Features of Enterovirus Respiratory Infections in French Children between 1999 and 2005 - Jacques, Jérôme; Moret, Hélène; Minette, Delphine; Lévêque, Nicolas; Jovenin, Nicolas; Deslée, Gaetan; Lebargy, François; Motte, Jacques; Andréoletti, Laurent (Journal of Clinical Microbiology, 2008)
Enteroviruses (EVs) can induce nonspecific respiratory tract infections in children, but their epidemiological, virological, and clinical features remain to be assessed. In the present study, we analyzed 252 EV-related infection cases (median age of subjects, 5.1 years) diagnosed among 11,509 consecutive children visiting emergency departments within a 7-year period in the north of France. EV strains were isolated from nasopharyngeal samples by viral cell culture, identified by seroneutralization assay, and genetically compared by partial amplification and sequencing of the VP1 gene. The respiratory syndromes (79 [31%] of 252 EV infections) appeared as the second most common EV-induced pediatric pathology after meningitis (111 [44%] of 252 cases) (44 versus 31%, P < 10⁻³), contributing to lower respiratory tract infection (LRTI) in 43 (54%) of 79 EV respiratory infection cases. Bronchiolitis was the most common EV-induced LRTI (34 [43%] of 79 cases, P < 10⁻³) occurring more often in infants aged 1 to 12 months (P = 0.0002), with spring-fall seasonality. Viruses ECHO 11, 6, and 13 were the more frequently identified respiratory strains (24, 13, and 11%, respectively). The VP1 gene phylogenetic analysis showed the concomitant or successive circulation of genetically distinct EV respiratory strains (species A or B) during the same month or annual epidemic period. Our findings indicated that respiratory tract infections accounted for the 30% of EV-induced pediatric pathologies, contributing to LRTIs in 54% of these cases. Moreover, the concomitant or successive circulation of genetically distinct EV strains indicated the possibility of pediatric repeated respiratory infections within the same epidemic season.